Fast Switching Liquid Crystal Display Modes - Hegde, Gurumurthy; Komitov, Lachezar (International Society for Optics and Photonics, 2012)
We present two LCD modes enabling short rise and fall switching time, being in the microsecond range in most of the modes. Polymeric network, created in the liquid crystal bulk, as well as in the presence of flexoelectric polarization are among those employed for achieving of fast switching modes in LCDs. Proper assembling and electronic driving of two parallel liquid crystal cells, arranged in a double cell configuration, is another approach enabling a fast switching mode between bright and dark state of the device. We discuss these modes in terms of device performance and their suitability for application in LCDs.